Acceptance and hesitancy of COVID-19 vaccine among Nepalese population: A cross-sectional study. - Suresh Dahal; Srishti Pokhrel; Subash Mehta; Supriya Karki; Harish Chandra Bist; Dikesh Kumar Sahu; Nimesh Lageju; Sagar Panthi; Durga Neupane; Ashish Shrestha; Tarakant Bhagat; Santosh Kumari Agrawal; et al. (PLoS ONE, 2022)
Introduction COVID-19 is an emerging infectious disease with a high transmission rate and substantial deaths. Various vaccines have been developed to combat it. This study is aimed to assess COVID-19 vaccine acceptance and hesitancy among the Nepalese population through a web-based survey. Materials and methods This is a web-based cross-sectional descriptive study of Nepalese people 18 years and above from different regions of Nepal who use social media (Facebook, Twitter, Reddit) as well as instant messaging applications (Messenger, Viber, WhatsApp). The duration of the study was 3 months from 1st June 2021 to 31st August 2021. The sampling technique used was self-selected non-probability sampling. A validated questionnaire had been taken to record the data. Results A total of 307 participants were included in the study. About three-fourths of participants 231 (75.2%) had not been vaccinated while 76 (24.8%) had been vaccinated with COVID -19 vaccine. Out of 231 non-vaccinated participants, most of participants 213 (92.2%) had shown acceptance of the COVID-19 vaccine. More than two-thirds of participants believed that the vaccine would protect them, their family members, and the community from having COVID-19 in the future. Very few participants 18 (7.2%) were hesitant to receive the vaccine against COVID-19. About two-thirds of participants were being afraid of adverse effects of the COVID-19 vaccine while more than half of participants hesitated due to lack of enough information regarding COVID-19 vaccine. Conclusion This study can aid in the planning of vaccination campaigns and the direction of future public health efforts aimed at increasing COVID-19 vaccine uptake.